A situação atual do ensino médio brasileiro e as propostas para a próxima década: infraestrutura, gestão e formação do profissional que atua no ensino médio - Brandao, Carlos da Fonseca [UNESP] (My University, 2012)
The aim of this paper is to analyze the current brazilian high school situation that refers specifically to issues of infrastructure, training of professionals working in high school and the question of management of high school, because we believe that such questions also may have fundamental importance for both young people who drop out of high school and for young people who stay there. We will discuss these issues (infrastructure, management and training of professionals working in high school) as a reference, on the one hand, the goals and objectives proposed by the last National Education Plan (PNE - Law No. 10.172/2001), and on the other hand, the objectives and goals proposed for these same issues by the new PNE, to run until 2020, emphasizing that this is still under discussion in Congress, therefore, liable to modifications.

O objetivo desse artigo é fazer uma análise da situação atual do Ensino Médio no que se refere especificamente às questões de infraestrutura, da forma- ção do profissional que atua neste nível e da questão da gestão do Ensino Médio, por entendermos que tais questões também podem ter fundamental importância tanto para os jovens que se evadem do Ensino Médio quanto para os jovens que nele permanecem. Analisaremos essas questões (infraestrutura, gestão e forma- ção do profissional que atua no Ensino Médio), tendo como referência, por um lado, os objetivos e metas propostos pelo último Plano Nacional de Educação (PNE – Lei nº 10.172/2001) e por outro lado, os objetivos e metas propostos para essas mesmas questões pelo novo PNE, a vigorar até 2020, ressaltando que este ainda se encontra em fase de discussão no Congresso Nacional, portanto, passível de modificações.
The current situation of brazilian high school and proposals for the next decade: infrastructure, management and vocational training of professional working in that level
Keywords: High school; Brazilian educational policy; The National Education Plan; Ensino Médio; Plano Nacional de Educação; Plano de Desenvolvimento da Educação; Gestão educacional; Formação profissional; Formação docente